Freedom from Violence and Lies Essays on Russian Poetry and Music - Karlinsky, Simon (Ars Rossica, 2013)
Freedom from Violence and Lies is a collection of forty-one essays by Simon Karlinsky (1924-2009), a prolific and controversial scholar of modern Russian literature, sexual politics, and music who taught in the University of California, Berkeley's Department of Slavic Languages and Literatures from 1964 to 1991. Among Karlinsky's full-length works are major studies of Marina Tsvetaeva and Nikolai Gogol, Russian Drama from Its Beginnings to the Age of Pushkin; editions of Anton Chekhov's letters; writings by Russian émigrés; and correspondence between Vladimir Nabokov and Edmund Wilson. Karlinsky also wrote frequently for professional journals and mainstream publications like the New York Times Book Review and the Nation. The present volume is the first collection of such shorter writings, spanning more than three decades. It includes twenty-seven essays on literary topics and fourteen on music, seven of which have been newly translated from the Russian originals.